(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Congenital fusion of atlas to the basiocciput is defined as atlanto-occipital assimilation/occipitalization of atlas. Case report: During the norma basalis demonstration session of skull, we have noticed an assimilation/occipitalization of atlas vertebra. Atlas fusion may be complete or partial; assimilation of atlas is associated with neurovascular and skeletal anomalies. Conclusion: Atlanto-occipital fusion may reduce the dimensions of foramen magnum thereby leads to brain stem compression causing the consequent neurological complications. Present case may pose difficulty in performing cisternal puncture. This anomaly has high clinical significance as it mimics the Arnold Chiari malformation. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.169-171